2021
DOI: 10.1038/s41598-021-95189-y
|View full text |Cite
|
Sign up to set email alerts
|

Element-specific contributions to improved magnetic heating of theranostic CoFe2O4 nanoparticles decorated with Pd

Abstract: Decoration with Pd clusters increases the magnetic heating ability of cobalt ferrite (CFO) nanoparticles by a factor of two. The origin of this previous finding is unraveled by element-specific X-ray absorption spectroscopy (XAS) and magnetic circular dichroism (XMCD) combined with atomic multiplet simulations and density functional theory (DFT) calculations. While the comparison of XAS spectra with atomic multiplet simulations show that the inversion degree is not affected by Pd decoration and, thus, can be e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recent studies have demonstrated that intra and inter-aggregate dipolar interaction effects are renowned for modifying the heating efficacy of the MNPs 20 . However, despite achieving magnetic nanoparticles with improved functionalities, dispersibility, and the challenge of obtaining MNPs with enhanced functionalities/dispersibility and high SAR still persists 21 , 22 . Notably, dextran and chitosan-coated Fe 3 O 4 MNPs stand out as excellent options for clinical trials in hyperthermia applications due to their non-antigenic, biocompatible, bio-functional, and biodegradable nature 17 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that intra and inter-aggregate dipolar interaction effects are renowned for modifying the heating efficacy of the MNPs 20 . However, despite achieving magnetic nanoparticles with improved functionalities, dispersibility, and the challenge of obtaining MNPs with enhanced functionalities/dispersibility and high SAR still persists 21 , 22 . Notably, dextran and chitosan-coated Fe 3 O 4 MNPs stand out as excellent options for clinical trials in hyperthermia applications due to their non-antigenic, biocompatible, bio-functional, and biodegradable nature 17 , 23 .…”
Section: Introductionmentioning
confidence: 99%